2007
DOI: 10.1016/j.sleep.2006.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Insights into REM sleep behavior disorder pathophysiology in brainstem-predominant Lewy body disease

Abstract: Background and purpose-Rapid eye movement (REM) sleep behavior disorder (RBD) is a parasomnia reflecting changes in the brain, but which specific neuronal networks are involved in human RBD pathogenesis has not yet been determined. To date, only one case of idiopathic RBD has undergone autopsy, in which "incidental Lewy body disease" was found. Due to the severe neuronal loss and gliosis in the substantia nigra (SN) and locus ceruleus (LC) in this case, degeneration of brainstem monoaminergic neurons was postu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
109
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(117 citation statements)
references
References 13 publications
6
109
0
2
Order By: Relevance
“…Third, the evaluation of RBD symptom severity was made according to the criteria set in the revised edition of ICSD-1. More comprehensive rating scales for RBD severity that have been published more recently must be used to evaluate RBD symptoms (Boeve et al 2007;Stiasny-Kolster et al 2007;Li et al 2010). …”
Section: Discussionmentioning
confidence: 99%
“…Third, the evaluation of RBD symptom severity was made according to the criteria set in the revised edition of ICSD-1. More comprehensive rating scales for RBD severity that have been published more recently must be used to evaluate RBD symptoms (Boeve et al 2007;Stiasny-Kolster et al 2007;Li et al 2010). …”
Section: Discussionmentioning
confidence: 99%
“…We previously reported pathologic findings in iLBD, including decreased nigrostriatal dopaminergic innervation, that suggest that it may be presymptomatic PD rather than merely an incidental age-related change [6]. Boeve and coworkers reported on a patient with idiopathic RBD with brainstem Lewy bodies, but no significant neuronal loss in the substantia nigra, again consistent with iLBD [3]. Only a few studies have reported prodromal symptoms before presentation of overt clinical signs of MSA.…”
Section: Discussionmentioning
confidence: 77%
“…Parenthetically, not all PD-related sleep disorders are linked to dopamine deficiency. Rapid eye movement sleep behavior disorder is a primary symptom of Lewy body disorders, 22 manifest as acting-out dreams. It may precede PD by many years 23 and is treated with a bedtime dose of a benzodiazepine (clonazepam).…”
Section: Levodopa Dyskinesias Are Often Benign and Treatablementioning
confidence: 99%